ANTIMICROBIAL IMMUNITY CONDITION IN PATIENTS WITH PURULENT MAXILLARY SINUSITIS - Ognivenko, E.V.; Popov, N.N.; Romanova, E.A. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
Antimicrobialimmunitycondition has been examined in 29 patients with purulentmaxillarysinusitis in the exacerbation phase under insulin-dependent diabetes mellitus (group 1) and 29 chronic purulentmaxillarysinusitis patients not suffering from endocrinopathies of any kind (group 2)/ Development of purulentmaxillarysinusitis in persons insulin-dependent diabetes mellitus progresses against the background of the significant decrease of the main antimicrobialimmunity factors aktivity, affinity of the produced antibodies, opsonizing properties of serum, and phagocytic biocidal activity of neutrophils.Neutrophil biocidity decrease is associated with malfunctions occurring in both oxygen-dependent and oxygen-independent ntimicrobial mechanisms.